2016
DOI: 10.1002/cbin.10589
|View full text |Cite
|
Sign up to set email alerts
|

A protease‐activated receptor 2 agonist (AC‐264613) suppresses interferon regulatory factor 5 and decreases interleukin‐12p40 production by lipopolysaccharide‐stimulated macrophages: Role of p53

Abstract: The transcription factor interferon regulatory factor 5 (IRF5) has a key role in the production of interleukin (IL)-12 by macrophages. IRF5 is also a central mediator of toll-like receptor signaling and is a direct target of p53. Activation of protease-activated receptor 2 (PAR-2) upregulates p53 and suppresses apoptosis. This study investigated the influence of human neutrophil elastase (HNE) and PAR-2 agonists on expression of IRF5 and IL-12p40 by macrophages stimulated with lipopolysaccharide. Granulocyte-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Surprisingly, a nonpeptide agonist (AC-264613) significantly upregulated PS levels rather than HNE (Figure 1b). We previously reported that AC-264613 significantly reduced p53 protein expression [24], and p53 activation is known to induce PS externalization early in apoptosis [25].…”
Section: Resultsmentioning
confidence: 92%
“…Surprisingly, a nonpeptide agonist (AC-264613) significantly upregulated PS levels rather than HNE (Figure 1b). We previously reported that AC-264613 significantly reduced p53 protein expression [24], and p53 activation is known to induce PS externalization early in apoptosis [25].…”
Section: Resultsmentioning
confidence: 92%